Analysis of Export, Investment, and Corruption Perceptions’ Influence on GDP Per Capita of 5 Emerging Countries in ASEAN - Arina Nur Fitri; Muhammad Yudhi Lutfi (Universitas Nahdlatul Ulama Sidoarjo, 2024)
The purpose of this study is to examine how the GDP per capita of 5 ASEAN countries is impacted by exports, investment, and perceptions of corruption. Indonesia, Thailand, Malaysia, the Philippines, and Vietnam are included in this study and categorized as emerging ASEAN. Panel data regression using the Fixed Effect Model (FEM) is the technique employed in this study. The results show that the GDP per capita of the 5 ASEAN countries is significantly impacted by exports and the perception of corruption. Exports are significant at the 5% level whereas the perception of corruption is important at the 10% level. Exports of good and services and low corruption rates will bring the increase of GDP per capita of 5 ASEAN countries. However, investment has found to negatively effect GDP per capita of 5 ASEAN countries. Evaluation of the effectiveness of investment related policies are needed to maximize the spillover effects of investment so it can have positive impact on the economy.